IMPLEMENTATION OF LEGAL STUDIES LEARNING FOR EARLY CHILDHOOD EDUCATION AT RA KAWAKIBI DELI SERDANG - Rahimah, Rahimah; Koto, Ismail (NOMOI Law Review, 2023)
This research was conducted to determine the legal learning strategies and models for early childhood education which were implemented at RA Kawakibi Deli Serdang . This research uses a qualitative case study method, uses the Miles Hubberman model analysis technique. This research was conducted at RA Kawakibi Deli Serdang . The focus of this research is on models of learning legal aspects for young children, with the hope of internalizing and increasing understanding of legal values from an early age, so that young children are able to implement legal values both in the family , school and community environments, as quoted by Zeece states that the development of children's sensitivity and understanding of what other people think, feel and do is important for the effective functioning of their social world. This understanding is able to enable children to recognize, organize and explain, and sometimes predict, the behavior of other people ( Zeece , 2000). Based on research conducted, the legal learning model for early childhood is: (1) introducing law in the simplest way, (2) integrated with learning in other aspects, (3) learning in a contextual way. Meanwhile, the influencing factors are: (1) teachers' knowledge of the law, (2) parents' knowledge of the law, and (3) capacity and ability to be responsible for the law.